Mast cells enhance sterile inflammation in chronic nonbacterial osteomyelitis - Stephanie Young; Namit Sharma; Jae Hoon Lee; Violeta Chitu; Volker Neumeister; Elisabeth Sohr; E. Richard Stanley; Christian M. Hedrich; Andrew W. B. Craig (The Company of Biologists, 2019)
Chronic nonbacterial osteomyelitis (CNO) is an autoinflammatory bone disease, and patients with active or recurrent bone inflammation at multiple sites are diagnosed with chronic recurrent multifocal osteomyelitis (CRMO). The Chronic multifocal osteomyelitis (CMO) mouse model develops IL-1β-driven sterile bone lesions reminiscent of severe CRMO. The goal of this study was to evaluate the potential involvement of mast cells in CMO/CRMO. Here, we show that mast cells accumulate in inflamed tissues from CMO mice and that mast cell protease Mcpt1 can be detected in the peripheral blood. A transgenic model of connective tissue mast cell depletion (Mcpt5-Cre:Rosa26-Stopfl/fl-DTa) was crossed with CMO mice and the resulting mice (referred to as CMO/MC-) showed a significant delay in disease onset compared with age-matched CMO mice. At 5-6 months of age, CMO/MC- mice had fewer bone lesions and immune infiltration in the popliteal lymph nodes that drain the affected tissues. In bone marrow-derived mast cell cultures from CMO mice, cytokine production in response to the alarmin IL-33 was elevated compared with wild-type cultures. To test the relevance of mast cells to human CRMO, we tested serum samples from a cohort of healthy controls and from CRMO patients at diagnosis. Interestingly, mast cell chymase was elevated in CRMO patients as well as in patients with oligoarticular juvenile arthritis. Tryptase-positive mast cells were also detected in bone lesions from CRMO patients and patients with bacterial osteomyelitis. Together, our results identify mast cells as cellular contributors to bone inflammation in CMO/CRMO and provide rationale for further study of mast cells as therapeutic targets.